The Teacher’s Professional Development Process in the Professional Learning Community in Thailand and in Foreign Countries: กระบวนการพัฒนาวิชาชีพครูแบบชุมชนแห่งการเรียนรู้ทางวิชาชีพ ในประเทศไทยและต่างประเทศ - Wangkaewhiran, Thipwimol; Meesuk, Parinya; Wongrugsa, Angwara (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ กระบวนการพัฒนาวิชาชีพครูแบบชุมชนแห่งการเรียนรู้ทางวิชาชีพมีพัฒนาการมาจากกลยุทธ์ระดับองค์กรที่มุ่งเน้นให้องค์กรมีการปรับตัวต่อกระแสการเปลี่ยนแปลงของสังคมที่เกิดขึ้นอย่างรวดเร็ว โดยเริ่มพัฒนาจากแนวคิดองค์กรแห่งการเรียนรู้ และปรับประยุกต์ให้มีความสอดคล้องกับบริบทของหน่วยงานที่นาไปใช้รวมถึงสถานศึกษา โดยมีเป้าหมายเพื่อขับเคลื่อนการเรียนรู้ร่วมกันทางวิชาชีพ สาหรับการนา PLC มาใช้ในวงการศึกษา ให้ประสบความสาเร็จเริ่มต้นจากการมีความเชื่อพื้นฐานของผู้มีส่วนได้ส่วนเสียร่วมกัน โดยมีความเชื่อว่า PLC เป็นกระบวนการเชิงเครื่องมือที่ช่วยสนับสนุนการดาเนินงานพัฒนาเชิงรุกให้ประสบความสาเร็จได้ โดยที่การดาเนินงานนั้นสามารถขับเคลื่อนได้หลากหลายวิธีการ อาทิ การศึกษาบทเรียนร่วมกัน (lesson Study) หรือ การวิจัยเชิงปฏิบัติการในชั้นเรียน (Action Research) นอกจากนั้น การมีปัจจัยสนับสนุนเชิงระบบที่อาศัยความร่วมมือกับเครือข่ายผู้มีส่วนได้ส่วนเสียกับการผลิตและใช้ครูจะช่วยส่งเสริมให้ PLC เป็นกลยุทธ์ที่ช่วยสนับสนุนส่งเสริมการพัฒนาครู อันเป็นปัจจัยสาคัญในการสร้างคุณค่าและมูลค่าของการศึกษาในเชิงเศรษฐศาสตร์ที่มีเป้าหมายเพื่อสร้างคนคุณภาพที่สามารถประกอบอาชีพได้อย่างมีประสิทธิภาพอันเป็นปัจจัยพื้นฐานที่ส่งผลต่อการพัฒนาเศรษฐกิจของประเทศต่อไป ABSTRACT The idea of teachers’ professional development process through the professional learning community (PLC) developed from organization strategy, which focuses on the organization adapted to the rapid changes in society. The PLC began to develop from the concept of the learning organization and then was adapted to be consistent with the context of the organization, including educational institutions. The goal of the PLC is to drive professional learning. The successful introduction of the PLC used in education began with the basic beliefs of common stakeholders. It is believed that the PLC is a process-oriented tool that has supported proactive development successfully. The operation can be driven in a variety of ways, such as lesson study or action research. There are also system support factors that rely on collaboration with networks of stakeholders-learners, teachers, and universities. The PLC is a strategy supporting teachers’ development, which is an important factor in creating value for the economics of education with the goal of creating quality people to be able to work efficiently and to support the country’s economic development.